2011
DOI: 10.1007/s11033-011-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

Absence of JAK2V617F mutation in patients with beta-thalassemia major and thrombocytosis due to splenectomy

Abstract: The report of Janus Kinase 2 (JAK2) mutations in myeloid malignancies with high frequency in myeloproliferative neoplasms has been well known since 2005. By monitoring allele burden, it is found that the expression of JAK2V617F mutation is increasing significantly from essential thrombocytosis to polycythemia vera. Furthermore, JAK2 abnormalities are reported in the majority of unexplained thrombotic episodes. Thalassemic syndromes are characterized by ineffective erythropoiesis and thrombocytosis, mainly due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…11 JAK2 mutation analysis is also helpful when investigating MPN since it is mainly positive in MPN, 1 , 11 but absent in thalassemia major patients with thrombocytosis due to splenectomy. 13 This case report illustrates the serious thrombotic complications of PV found in a splenectomized thalassemic patient. Acute myocardial infarction events were reported in both PV and beta-thalassemia major.…”
Section: Discussionmentioning
confidence: 81%
“…11 JAK2 mutation analysis is also helpful when investigating MPN since it is mainly positive in MPN, 1 , 11 but absent in thalassemia major patients with thrombocytosis due to splenectomy. 13 This case report illustrates the serious thrombotic complications of PV found in a splenectomized thalassemic patient. Acute myocardial infarction events were reported in both PV and beta-thalassemia major.…”
Section: Discussionmentioning
confidence: 81%
“…It can be postulated that higher levels of Epo result in increased stimulation of the EpoR/JAK2/STAT5 signaling pathway, thus increasing the probability of JAK2 mutations occurring as a result of increased transcriptional activity of the JAK2 gene. [11]. At variance with these negative results, Asadi et al have recently detected this mutation in 19% of 75 patients with beta-thalassemia major [12].…”
Section: Discussionmentioning
confidence: 98%
“…There is a high turnover of red blood cells behaving under stress in an erythropoiesis-like situation[ 3 , 4 ] There have been some case studies showing an association between beta thalassemia and PV. [ 5 ] The review of the literature showing cases of beta-thalassemia trait with PV are shown in Table 1 [ 1 , 6 7 8 9 10 ] It is possible that chronic stress erythropoiesis which is associated with beta thalassemia can lead to ineffective erythropoiesis and also increase the risk of somatic JAK2 mutation. [ 1 , 5 ] More prospectives are needed to find out the correlation between thalassemia trait and PV.…”
Section: Discussionmentioning
confidence: 99%